Computational Analysis Of 2d Aerospike Nozzle With Base Bleed At Different Altitudes - et. al., Santhosh Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the present-day scenario, several nozzles are being developed to achieve better efficiency. Among them, the aerospike is one such nozzle. The aerospike nozzles are yet to be utilized in the aerospace sector but are believed to exhibit better performance than the conventional bell-shaped nozzles that are currently in service. The geometry of the aerospike nozzle enables it to adjust to its environment by modifying its outer jet boundary thus, making it more efficient than the other types of nozzles. Simple approximation method is used to get the coordinates of the nozzle contour using MATLAB. To compare the performance characteristics, both full and truncated spike nozzles were designed using SOLIDWORKS. In order to improve the performance of the truncated aerospike nozzles, they are provided with base bleeds. The flow behaviour was analysed using Computational Fluid Dynamics (CFD) software – ANSYS. These designs were simulated for different pressure outlet conditions, to compare the performance of full length, truncated spike with and without base bleed, at different altitudes.